Genomic analysis of Escherichia coli strains isolated from diseased chicken in the Czech Republic - Aneta Papouskova; Martina Masarikova; Adam Valcek; David Senk; Darina Cejkova; Eva Jahodarova; Alois Cizek (BMC Veterinary Research, 2020)
Abstract Background Avian pathogenic Escherichia coli (APEC) can cause various extraintestinal infections in poultry, resulting in massive economic losses in poultry industry. In addition, some avian E. coli strains may have zoonotic potential, making poultry a possible source of infection for humans. Due to its extreme genetic diversity, this pathotype remains poorly defined. This study aimed to investigate the diversity of colibacillosis-associated E. coli isolates from Central European countries with a focus on the Czech Republic. Results Of 95 clinical isolates subjected to preliminary characterization, 32 were selected for whole-genome sequencing. A multi resistant phenotype was detected in a majority of the sequenced strains with the predominant resistance to β-lactams and quinolones being associated with TEM-type beta-lactamase genes and chromosomal gyrA mutations respectively. The phylogenetic analysis confirmed a great diversity of isolates, that were derived from nearly all phylogenetic groups, with predominace of B2, B1 and C phylogroups. Clusters of closely related isolates within ST23 (phylogroup C) and ST429 (phylogroup B2) indicated a possible local spread of these clones. Besides, the ST429 cluster carried bla CMY-2, − 59 genes for AmpC beta-lactamase and isolates of both clusters were generally well-equipped with virulence-associated genes, with considerable differences in distribution of certain virulence-associated genes between phylogenetically distant lineages. Other important and potentially zoonotic APEC STs were detected, incl. ST117, ST354 and ST95, showing several molecular features typical for human ExPEC. Conclusions The results support the concept of local spread of virulent APEC clones, as well as of zoonotic potential of specific poultry-associated lineages, and highlight the need to investigate the possible source of these pathogenic strains.